Variables de gestión para un modelo policial a partir del marco de la seguridad pública sustentable. Caso Michoacán, México - García Torres, Arón (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
The present research was carried out with the objective of determining the management variables that would characterize a police model for the state of Michoacán starting from conceptualizing the management of a sustainable public security. Such variables are the following: 1. Approach to security as a human right and a basic human need; 2. Appropriate legal frameworks; 3. Professionalization and training for public service and management; 4. Permanent and continuous evaluation of processes and personnel; 5. Decent and fair working conditions; 6. Strategic and participatory management; 7. Sensitivity to the context with a human approach and community bases; 8. Transparency and accountability in operational strategies and in the use of resources; and 9. A police profile adequate to local conditions. Which was reached from the analysis of the different concepts of security developed and international experiences about successful police models in contrast to the actions implemented and the results obtained with the police management models established by the government to address the problems of insecurity in Michoacán.

La presente investigación se realizó con el objetivo de determinar las variables de gestión que caracterizarían a un modelo policial para el estado de Michoacán partiendo de conceptualizar la gestión de una seguridad pública sustentable. Tales variables son las siguientes: 1. Enfoque de la seguridad como un derecho humano y una necesidad humana básica; 2. Marcos jurídicos adecuados; 3. Profesionalización y capacitación para el servicio y la gestión pública; 4. Evaluación permanente y continúa de procesos y personal; 5. Condiciones laborales dignas y justas; 6. Gestión estratégica y participativa; 7. Sensibilidad al contexto con enfoque humano y bases comunitarias; 8. Transparencia y rendición de cuentas en las estrategias operativas y en el uso de los recursos; y 9. Un perfil policial adecuado a las condiciones locales. A las cuales se llegó a partir del análisis de los distintos conceptos de seguridad desarrollados y de las experiencias internacionales acerca de modelos policiales exitosos en contraste con las acciones implementadas y los resultados obtenidos con los modelos de gestión policial establecidos por el gobierno para atender los problemas de inseguridad en Michoacán.
Facultad de Economía Vasco de Quiroga. Maestría en Gestión Pública de la Sustentabilidad
Keywords: info:eu-repo/classification/cti/5; FEVAQ-M-2018-0374; Modelo policial; Sustentabilidad; Desarrollo a escala humana; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5017